Trends Research Characterization of TiO2 Thin Films as Solar Cell Materials (2015-2024): A Systematic Review - Aris Doyan; Susilawati; Muhammad Taufik; Syarful Annam (Postgraduate, University of Mataram, 2024)
Research in the field of solar cells continues to increase along with the development of the times and human needs for renewable energy sources. One of the fields of study that is often used as a research topic is the development of Thin Film Solar Cells or known as Thin Film Solar Cells (TFSC). This research aims to identify and analyze research trends of synthesis of Ti02 thin films as solar cell materials. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research on synthesis of Ti02 thin films as solar cell materials that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend on synthesis of TiO2 thin films as solar cell materials indexed by Google Scholar from 2015 to 2024 has experienced increases and decreases. There are many documents in the form of articles, proceedings, chapters, preprints, monograph and edited books that discuss research about synthesis of Ti02 thin films as solar cell materials. Key words that are often used in research about it are dye sensitized cell, electrode, electron, characterization, etc.